Pemulihan Ekonomi Jepang pasca The Great East Japan Earthquake melalui Kebijakan Comprehensive Special Zone for International Competitiveness - ARYATI, ANNISA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Great East Japan Earthquake that happened on Tohoku on March 11th 2011 has been destruct all over East Japan. Japan economy collapsed all of sudden because of the destructive damage from tsunami that came after and nuclear disaster from Fukushima Daiichi nuclear reactor meltdown. The government tried to make a comprehensive policy to solve the after effect of earthquake and consider about Japan economic problem or the Lost Decade. After all consideration, on December 22nd 2011 Prime Minister Yoshiko Noda came along with the strategy âOvercoming Crises and Embarking on New FrontiersâThe Strategy for Rebirth of Japan.â The interested policy from that strategy is Comprehensive Special Zone for International Competitiveness. Japan known as the state that implemented capitalist developmental state system, but what is the reason behind that policy so then Japan confident to open their market and receive a lot of foreign direct investment. Is it the comprehensive special zone effective to recover Japan economic from the after effect of earthquake?